The contribution of instructional leadership and followership styles to the teachers’ performance in elementary school - Eka Wira Putra; Rusdinal Rusdinal; Yahya Yahya (International Conferences on Educational, Social Sciences and Technology)
The objectives of the research are to find out and explain, the contribution of instructional leadership to the teachers’ performance, contribution followership style to the teachers’ performance, contribution of instructional leadership and followership style to teachers’ performance in elementary school in Batahan district. This research using quantitative method with correlational approaches. The population is all the civil servant teachers in elementary school in Batahan district 110 teachers. Sample are 59 teachers by stratified proportional random sampling technique. The instrument use likert scale and the reliability 0,944. Data analysis technique is processed by using correlation and regression with help of SPSS version 20 program. Based on the analysis results can be concluded as follows: instructional leadership contributes significantly to the teachers’ performance, followership style contributes significantly to the teachers’ performance, instructional leadership and followership style contribute significantly to teachers’ performance in elementary school in Batahan district Mandailing Natal regency, North Sumatera.